ANALISIS KINERJA, HARGA POKOK PRODUKSI DAN KEUNTUNGAN AGROINDUSTRI TAHU DI PEKON GADINGREJO KECAMATAN GADINGREJO KABUPATEN PRINGSEWU - Ningsih, Surati Mei; Murniati, Ktut; Yanfika, Helvi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
This study aims to analyze the performance of production and cost of goods produced in the tofu agroindustry in Pekon Gadingrejo, Gadingrejo District, Pringsewu Regency. The research locations were carried out in three tofu agroindustries located in Pekon Gadingrejo, Gadingrejo District, Pringsewu Regency, which was chosen intentionally (purposively) with the consideration that the pekon in Gading Rejo District is a tofu production center in Pringsewu Regency. The respondents in this study were owners of agroindustries. The data analysis used is descriptive qualitative and quantitative. Analysis of data is cost of goods produced using full costing analysis. The results showed that the production performance in the three agro-industries of tofu in Pekon Gadingrejo, Gadingrejo District, Pringsewu Regency, based on productivity, capacity, quality, process speed, and delivery speed was good, but based on flexibility indicators, it was not yet oftimal, because there was no other products produced from the same raw materials. As a result of the calculation of the cost of goods produced, the three agro-industries know are profitable and worthy of development. The biggest advantage is in the type of tofu pong. Keywords : cost of production, production performance, tofu.